Two decades of Iranian midwives' activities as a health care provider under supervision in a multidisciplinary team in reducing maternal mortality - Mojgan Mirghafourvand; Shahla Khosravi; Jafar Sadegh Tabrizi; Azam Mohammadi; Parvin Abedi (BMC, 2021)
Abstract Iran is amongst the countries that have achieved the fifth goal of the United Nations Millennium Development Goal. The maternal mortality ratio (MMR) in Iran has declined from 48 cases per 100,000 in 2000 to 16 cases per 100,000 in 2017, showing an annual decline rate of about 6.3%. In the International Year of the Nurse and the Midwife (year 2020), this commentary highlights two decades of Iranian midwives' activities as a health care provider under supervision in a multidisciplinary team in reducing maternal mortality.